Determining Priority Strategies for Meteorological Drought Disaster Mitigation in Bima Regency, West Nusa Tenggara - Tanti Prasetya Prima Dewi; Yohana Noradika Maharani; Johan Danu Prasetya; Eko Teguh Paripurno; Eko Murdiyanto (Journal of Applied Geospatial Information, 2026)
Drought is a recurring disaster with increasing frequency in Bima Regency, Indonesia. Budget efficiency measures have reduced the number of drought mitigation programs and beneficiaries, limiting the local government's ability to implement all proposed mitigation strategies simultaneously. This study aims to establish a priority-based decision-making framework for implementing meteorological drought mitigation strategies, thereby supporting more effective and targeted disaster risk reduction. The Analytic Hierarchy Process (AHP) was employed using Expert Choice 11 to evaluate mitigation priorities based on a hierarchical structure consisting of objectives, criteria, sub-criteria, and alternatives. Data were collected from 30 experts representing the Regional Disaster Management Agency (BPBD), the Meteorological, Climatological, and Geophysical Agency (BMKG), the Agriculture Office, the Public Works and Spatial Planning Office (PUPR), and drought-affected communities. The results indicate that technical feasibility and effectiveness are the most influential criteria in determining mitigation priorities. The final AHP synthesis ranks education and public awareness programs as the highest priority (17.8%), followed by groundwater well drilling and water pumping systems (16.9%), and rehabilitation and optimization of irrigation networks (16.7%). These findings provide a practical basis for integrating prioritized drought mitigation strategies into regional development planning, including the Regional Government Work Plan (RKPD), Strategic Plans (Renstra), the Regional Development Information System (SIPD), and the Disaster Contingency Plan (Renkon), ensuring more sustainable and effective meteorological drought risk management in Bima Regency.